2021
DOI: 10.1186/s12958-021-00753-w
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated microRNA let-7a accelerates apoptosis and inhibits proliferation in uterine junctional zone smooth muscle cells in adenomyosis under conditions of a normal activated hippo-YAP1 axis

Abstract: Background Let-7a is a small non-coding RNA that has been found to take part in cell proliferation and apoptosis. The hippo-YAP1 axis, known as a tumour suppressor pathway, also plays an important role in cell proliferation and apoptosis. YAP1, TAZ, and phospho-YAP1 play key roles in actions of the hippo-YAP1 axis. Adenomyosis (ADS) is a proliferative disease leading to a large uterus in patients with prolonged illness. Abnormal proliferation of smooth muscle cells (SMCs) in the uterine endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…These biological processes illustrate the altered proliferation and invasive capacity of both eutopic endometrial cells and EMI smooth muscle cells in adenomyosis. Meanwhile, targeted genes in the network were involved in various important signaling pathways, such as the MAPK signaling pathway, PI3K-Akt signaling pathway, Ras signaling pathway and Hippo signaling pathway, according to the KEGG analysis, which have also been shown to be involved in adenomyosis [47][48][49][50]. The results suggest that eutopic endometrium and EMI smooth muscle co-expression of circRNAs alters cellular activity and influences the development of uterine adenomyosis by regulating these important signaling pathways.…”
Section: Discussionmentioning
confidence: 92%
“…These biological processes illustrate the altered proliferation and invasive capacity of both eutopic endometrial cells and EMI smooth muscle cells in adenomyosis. Meanwhile, targeted genes in the network were involved in various important signaling pathways, such as the MAPK signaling pathway, PI3K-Akt signaling pathway, Ras signaling pathway and Hippo signaling pathway, according to the KEGG analysis, which have also been shown to be involved in adenomyosis [47][48][49][50]. The results suggest that eutopic endometrium and EMI smooth muscle co-expression of circRNAs alters cellular activity and influences the development of uterine adenomyosis by regulating these important signaling pathways.…”
Section: Discussionmentioning
confidence: 92%
“…Abnormal proliferation of SMC in the endometrium-myometrial junction area is an important cause of AM ( Huang et al, 2021 ), and the emergence of AM causes hyperplasia and hypertrophy of the surrounding SMC ( Zhai et al, 2020 ). Compared to the SMC in the normal uterus, the uterine SMC has hypertrophy and ultrastructural changes, which may have contractility effects on the myometrium ( Mehasseb et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report found that Let-7A level was decreased, while the YAP1 level was increased, in uterine junctional zone SMCs in adenomyosis. Up-regulated Let-7A affected the expression levels of the components of the hippo-YAP1 axis, accelerated apoptosis and inhibited proliferation of JZ SMCs [ 144 ]. These findings suggest that the Let-7A and hippo-YAP1 axis may act as important regulators in the proliferation of JZ SMCs and occurrence of adenomyosis.…”
Section: Etiology and Pathogenesis Of Adenomyosismentioning
confidence: 99%